Effect of Yogurt and Bifidobacterium on Cryptosporidium parvum Infection In Experiential Infected Mice - Mohammed, S.T.; Jabur, K.; Aja, H.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study aimed to collected 150 feces sample from calves suffering sever diarrhea ,then there were isolation and purification of Cryptosporidium parvum oocyst from samples contain it. These oocysts were used to induce experimental infection in the Immunosupperessed mice, then the mice treated by Bifidium bacteria , its supernatant and local yogurt were used for bacterial isolation.       This study showed that the local yogurt was the best treatment which led to stop oocyst shedding from the mice in the 8th day after treatment under sufficient treatment (89.72%) , at the same time the mice treated with bacteria stopped the oocyst shedding in the 9th day with sufficient treatment (81.40 %) , while its supernatant were stopped the oocysts shedding in the 10th day with sufficient treatment (43.4%).